2019
DOI: 10.1002/acp.3514
|View full text |Cite
|
Sign up to set email alerts
|

Static and dynamic seductive illustration effects on text‐and‐graphic learning processes, perceptions, and outcomes: Evidence from eye tracking

Abstract: SummaryThis study aimed to examine how different forms (still pictures vs. animations) of seductive illustrations impact text‐and‐graphic learning processes, perceptions, and outcomes. An eye‐tracking experiment of three groups (static, dynamic, and control) was conducted with 60 college and graduate students while learning with PowerPoint slides about infant motor development milestones. Prior knowledge, learning performance, learning perception, and visual attention were assessed by achievement tests, self‐r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 40 publications
4
17
1
Order By: Relevance
“…This might indicate that participants' attention was distracted away from task relevant features more often in the game condition. This is not particularly surprising as more task irrelevant features were present in this condition and is in line with previous studies investigating seductive details [93], [94]. Importantly, however, this did not affect performance indicating users' ability to pay attention to both relevant and rather irrelevant task elements.…”
Section: B Attentional Levelsupporting
confidence: 90%
See 1 more Smart Citation
“…This might indicate that participants' attention was distracted away from task relevant features more often in the game condition. This is not particularly surprising as more task irrelevant features were present in this condition and is in line with previous studies investigating seductive details [93], [94]. Importantly, however, this did not affect performance indicating users' ability to pay attention to both relevant and rather irrelevant task elements.…”
Section: B Attentional Levelsupporting
confidence: 90%
“…Although there were no performance differences between game and no-game condition, we observed differential eye movement patterns. Overall, participants made more fixations in the game condition than in the no-game condition, which is in line with other studies investigating user interface attractiveness [92] or seductive details [93], [94]. However, task relevant AOIs (AOI1, AOI2, AOI3 reflecting the number line, and AOI5 representing the to-be-solved fraction) were fixated less often in the game condition as compared to the non-game condition.…”
Section: B Attentional Levelsupporting
confidence: 89%
“…Eitel et al (2019) found negative effects of seductive details on learning outcomes in a condition in which students were not informed about the irrelevance of seductive details, compared to students warned about it, arguing that the irrelevant information distract attention from relevant information. Studies with eye‐tracking (Alemdag & Cagiltay, 2018; Korbach et al, 2017; Park et al, 2015; Tsai et al, 2019) have supported the attentional explanation. For example, Tsai et al (2019) compared the effects of static seductive illustrations (e.g., pictures rated high in emotional interest but irrelevant for learning) and dynamic seductive illustrations (e.g., the same pictures, animated as GIFs) on eye fixation patterns when studying the material, and on learning performance.…”
Section: Introductionmentioning
confidence: 97%
“…Studies with eye‐tracking (Alemdag & Cagiltay, 2018; Korbach et al, 2017; Park et al, 2015; Tsai et al, 2019) have supported the attentional explanation. For example, Tsai et al (2019) compared the effects of static seductive illustrations (e.g., pictures rated high in emotional interest but irrelevant for learning) and dynamic seductive illustrations (e.g., the same pictures, animated as GIFs) on eye fixation patterns when studying the material, and on learning performance. They found that participants watching the presentation with the dynamic illustrations paid more attention to and processed more deeply and more persistently these seductive items than did those in the static group.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation